The Role of Principal Leadership in Improving the Work Ethic of Islamic Religious Education Teachers (Pai) at SD Muhammadiyah 2 Sidoarjo - Abdul Gafur (International Consortium of Education and Culture Research Studies, 2021)
The teacher is the transformational media of all the knowledge needed by students. In addition, the role of teachers is very much needed especially in Islamic-based schools that always pay attention and prioritize students to continue their studies in college. To get closer and to build with high enthusiasm for the achievement of the priorities above, the researcher conducted research at second grade of Elementary School in Sidoarjo by knowing more about the leadership style of the principal in improving the work ethic of Islamic Education teachers. This study is entitled